Identification of a Novel p.Q1772X ANK1 Mutation in a Korean Family with Hereditary Spherocytosis - Han, Joo Hyung (PLoS One, 2015)
Hereditary spherocytosis (HS), a common form of inherited hemolytic anemia, is a heterogeneous group of disorders with regard to clinical severity, protein defects, and mode of inheritance. Causal mutations in at least five genes have been reported so far. Because multiple genes have been associated with HS, clinical genetic testing that relies on direct sequencing will be a challenge. In this study, we used whole exome sequencing to identify a novel nonsense mutation in ANK1 (p.Q1772X, NM_020476) that resulted in a truncated protein in a Korean patient with HS. Sanger sequencing confirmed the two affected individuals in the patient’s family were heterozygous for the mutation. This is the first report of a Korean family that carries an ANK1 mutation responsible for HS. Our results demonstrate that next generation sequencing is a powerful approach for rapidly determining the genetic etiology of HS.